2019
DOI: 10.1042/bsr20182101
|View full text |Cite|
|
Sign up to set email alerts
|

LncRNA ANRIL affects the sensitivity of ovarian cancer to cisplatin via regulation of let-7a/HMGA2 axis

Abstract: This paper tried to explore ANRIL expression in ovarian cancer and how it affects cisplatin-sensitivity of ovarian cancer cells via regulation of let-7a/high-mobility group protein A2 (HMGA2) axis. qRT-PCR was used to detect ANRIL and let-7a levels in ovarian cancer tissues and cell lines (SKOV3 and SKOV3/DDP). Then cells were randomly assigned into Blank, negative control siRNA, ANRIL siRNA, let-7a inhibitor, and ANRIL siRNA+let-7a-inhibitor groups. CCK-8 assay was applied for assessing cell viability of cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…When ceRNA acquires transcriptional activity, it competes for miRNA targets, binds to RISC complexes, which results in the separation of miRNA-RISC complexes from parent genes and increased parental gene expression 48 . Miao et al 49 . reported that in ovarian cancer, ANRIL could interact with let-7a to further reduce HMGA2 levels, which promoted the apoptosis and improved the cisplatin sensitivity of ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…When ceRNA acquires transcriptional activity, it competes for miRNA targets, binds to RISC complexes, which results in the separation of miRNA-RISC complexes from parent genes and increased parental gene expression 48 . Miao et al 49 . reported that in ovarian cancer, ANRIL could interact with let-7a to further reduce HMGA2 levels, which promoted the apoptosis and improved the cisplatin sensitivity of ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, DDP is an important drug for the therapy of OC, while OC cells prone to generate drug resistance in OC treatment. 24 Moreover, lncRNAs were proved to be associated with DDP resistance in OC. For example, Long et al confirmed that lncRNA GAS5 increased DDP-resistance and promoted OC cell growth through modulating MAPK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, although this effect has been less studied, some lncRNAs control cell metabolism by regulating key enzymes in metabolic pathways, contributing mainly to stimulating glycolysis instead of aerobic metabolism (the Warburg effect). In the glycolysis pathway from glucose to pyruvate, the expression of hexokinase 2, catalyzing the first step, is activated by LINC00504 [70]; NRCP activates the second enzyme in the pathway, glucose-6-phosphate isomerase [26]; after that, 6-phosphofructo-2-kinase/fructose-2,6-biphosphatase 2 is induced by LINC00092 [31]; in the fourth step catalyzed by aldolase, two forms of the enzyme, A and C, are activated by NRCP [26]. The final step is catalyzed by pyruvate kinase isozyme M2, which is activated by both LINC00504 and H19 [70,132].…”
Section: Lncrnas Implicated In Oc Development and Progressionmentioning
confidence: 99%
“…For instance, Linc00176 acts as a scaffold to keep BCL3 and p50 together (NF-κB family) and at the same time recruits this complex to the ceruloplasmin promoter to activate its expression [139]. Some reports of transcriptional regulation by lncRNAs do not fit this classification at all, as in the case of FAL1, which increases the stability of BMI (another subunit of PRC), thereby allowing epigenetic marking of the p21 gene to be silenced [31,42].…”
Section: Transcriptional Regulationmentioning
confidence: 99%
See 1 more Smart Citation